Desain Rancang Bangun Sistem Monitoring Irigasi Sawah Menggunakan ESP8266 Berbasis Android Dengan Mode Bot Telegram - Syarifuddin syarifuddin baco; Sajiah Sajiah; Suradi Suradi; Nurfadila Awalia A.; Wulandari Suluwetang (Journal of System and Computer Engineering (JSCE), 2023)
Abstract Irrigation is a system of damming water sources to irrigate paddy fields. One of the farmer's activities that is still manual is monitoring or supervising the water supply by opening and closing the gates of the bunds in conditions of shortage or excess of water in paddy fields. The purpose of this research is to design a rice field irrigation monitoring system using Android-based ESP8266 with Telegram Bot mode. The research method used is Research and Development, using flowcharts as problem solving, using block diagrams as a guideline for how the designed tool system works. The test results begin by activating the switch button, activating wifi on the smartphone, then activating the Telegram application to provide commands and monitoring information such as the water level to be detected by the ultrasonic sensor and the order to enter water into the paddy fields according to the size of the incoming water discharge detected through the sensor flow meters, in and out pumps will supply water in and out to paddy fields when land conditions are lacking and exceeding the water level limit. The conclusions drawn from research on rice field irrigation monitoring systems using Android-based ESP8266 with mode can help farmers in monitoring or supervising irrigation water in paddy fields with remote control and tool testing can work well as expected. Keywords: Irrigation, ESP8266, Ultrasonic Sensor, Flow Meter Sensor, Telegram Bot